2007
DOI: 10.1074/jbc.m606482200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Cytochrome b at the Ubiquinol Oxidation Site of Yeast Complex III

Abstract: The cytochrome bc 1 complex is a dimeric enzyme of the inner mitochondrial membrane that links electron transfer from ubiquinol to cytochrome c by a protonmotive Q cycle mechanism in which ubiquinol is oxidized at one center in the enzyme, referred to as center P, and ubiquinone is rereduced at a second center, referred to as center N. To better understand the mechanism of ubiquinol oxidation, we have examined catalytic activities and pre-steady-state reduction kinetics of yeast cytochrome bc 1 complexes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 30 publications
5
50
0
Order By: Relevance
“…It was previously shown that Y279A, C, and S mutant enzymes exhibited a low SO production, a finding very similar to that observed here (24). Similar observations were reported using Rhodobacter capsulatus Y279 mutants (25).…”
Section: Figsupporting
confidence: 91%
“…It was previously shown that Y279A, C, and S mutant enzymes exhibited a low SO production, a finding very similar to that observed here (24). Similar observations were reported using Rhodobacter capsulatus Y279 mutants (25).…”
Section: Figsupporting
confidence: 91%
“…The second proton is extracted from the semiquinone by a conserved Glu272 (15-17) residue on the ef-loop connecting the "E" and "F" transmembrane helix (TMH), which are part of the -PEWY-sequence (18) located within the C-terminal domain of cytochrome b subunit of bc 1 (Glu272 in Rhodobacter sphaeroides bc 1 , and Glu78 in M. laminosus b 6 f). The crystal structures of the bc 1 complex obtained in the presence of quinol and quinone analogs show that after extraction of the second proton, the Glu272 residue undergoes a rotation (12,13,15,17,(32)(33)(34)(35) to move away from the Q p -site to face a water chain leading to the p-side aqueous phase to provide a route for proton exit. The 3.0-Å crystal structure of the b 6 f complex from M. laminosus shows the His129 residue (22) of the ISP soluble domain in a similar functional role as the His161 residue of the bc 1 ISP soluble domain.…”
Section: Resultsmentioning
confidence: 99%
“…The high conservation of Qo site surface residues in the terminal cavity is most likely to be driven by the requirement for precise positioning and binding of the ubiquinol substrate in the active site important for its undisturbed oxidation. For instance, the mutations Y279A and F129K in yeast substantially lower the enzyme activity to below 30% of wild-type turnover 51 . In addition, these mutations result in bypass reactions that generate deleterious reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%